2011
DOI: 10.1086/662162
|View full text |Cite
|
Sign up to set email alerts
|

Species Interactions Mediate Phylogenetic Community Structure in a Hyperdiverse Lizard Assemblage from Arid Australia

Abstract: Evolutionary history can exert a profound influence on ecological communities, but few generalities have emerged concerning the relationships among phylogeny, community membership, and niche evolution. We compared phylogenetic community structure and niche evolution in three lizard clades (Ctenotus skinks, agamids, and diplodactyline geckos) from arid Australia. We surveyed lizard communities at 32 sites in the northwestern Great Victoria Desert and generated complete species-level molecular phylogenies for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 86 publications
2
71
0
Order By: Relevance
“…Traits determining the β-niche (e.g., environmental tolerances, macro-habitat requirements) often show different evolutionary patterns than those determining the α-niche (e.g., resource partitioning, micro-habitat use), because coexisting species must evolve similarities in the former and differences in the latter [11], [12], [14], [76], [77], [78]. In our study, however, we found that phylogenetic signal varies not only between the broad categories of β-niche and α-niche traits, but also within those categories.…”
Section: Resultsmentioning
confidence: 99%
“…Traits determining the β-niche (e.g., environmental tolerances, macro-habitat requirements) often show different evolutionary patterns than those determining the α-niche (e.g., resource partitioning, micro-habitat use), because coexisting species must evolve similarities in the former and differences in the latter [11], [12], [14], [76], [77], [78]. In our study, however, we found that phylogenetic signal varies not only between the broad categories of β-niche and α-niche traits, but also within those categories.…”
Section: Resultsmentioning
confidence: 99%
“…*P<0.05; **P<0.01. ecosystems (Pianka, 1986;Pianka, 1989;Vitt et al, 2003). Ecological and phylogenetic structure studies have provided evidence supporting this hypothesis based on diet and habitat utilisation (Daly et al, 2008;Rabosky et al, 2011). Microhabitat specialisation has also been proposed as an underlying cause of the convergence of the species belonging to genus Ctenophorus into three morphologically distinct, albeit phylogenetically unrelated ecomorphs: burrowers, rock dwellers and spinifex/sand specialists (Greer, 1989;Melville et al, 2001;Hugall et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…With lizard lineages in Arid Australia, Rabosky et al (2011) demonstrated that accounting for lineages in community assembly may readily reveal the ecological traits associated with habitat preferences. In this context, other plausible explanations may be linked to key aspects of the species’ ecology given the intricate nature of the Alps.…”
Section: Discussionmentioning
confidence: 99%